External Risk in Design-Build Projects with Fixed-Price System: The Case of DKI Jakarta Province, Indonesia - Lindawati; Wibowo, Ari (International Journal of Science, Technology & Management, 2021)
The construction industry is a leading economic sector in the province of DKI Jakarta that positively contributes to its economic growth. As a province with the highest construction value in Indonesia, it used the design-build (DB) method as a project delivery system to optimize infrastructure projects. However, the DB project in DKI Jakarta had experienced some completion delays that could lead to project costs overrun. This study used a concurrent embedded (mixed method) design, with quantitative as the primary approach. The data collected through interviews, documentary studies, and questionnaire surveys of 50 practitioners in the construction field. This study found that utility disruption negatively influenced time and cost performance, while third-party risk did not affect. Besides, there was inadequate and inaccurate information conveyed to the contractor. It caused inappropriate risk identification that influenced the design, methods, and a working schedule that affected project performance. Furthermore, to ensure optimal project delivery, the government, as the project owner, needed to validate the information provided and coordinated the disruption handling before the project began.